let f(x)=5x-1and g(x)=x^2-4

Find (fog)(2)=

Simplify

1 answer

To find (fog)(2), we need to first find g(2) and then plug that value into f(x).

Step 1: Find g(2)
g(x) = x^2 - 4
g(2) = 2^2 - 4
g(2) = 4 - 4
g(2) = 0

Step 2: Plug g(2) into f(x)
f(x) = 5x - 1
f(g(2)) = 5(0) - 1
f(g(2)) = 0 - 1
f(g(2)) = -1

Therefore, (fog)(2) = -1.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. I have a take home test and I'm stuck on a couple. Anyone help please?1. Find the vertex & axis of symmetry: -5(x+4)^2-4 2. Find
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions